Clinical Practice Informs Secure Messaging Benefits and Best Practices - Haun, Jolie N.; Hathaway, Wendy; Chavez, Margeaux; Antinori, Nicole; Vetter, Brian; Miller, Brian K.; Martin, Tracey L.; Kendziora, Lisa; Nazi, Kim M.; Melillo, Christine (Applied Clinical Informatics, 2017)
Background Clinical care team members in Department of Veterans' Affairs (VA) facilities nationwide are working to integrate the use of Secure Messaging (SM) into care delivery and identify innovative uses. Identifying best practices for proactive use of SM is a key factor in its successful implementation and sustained use by VA clinical care team members and veterans.Objectives A collaborative project solicited input from VA clinical care teams about their local practices using SM to provide access to proactive patient-centered care for veterans and enhance workflow.Methods This project implemented a single-item cross-sectional qualitative electronic survey via internal e-mail to local coordinators in all 23 Veterans Integrated Service Networks (VISNs). Content analysis was used to manage descriptive data responses. Descriptive statistics described sample characteristics.Results VA clinical care team members across 15 of 23 VISNs responded to the questionnaire. Content analysis of 171 responses produced two global domains: (1) benefits of SM and (2) SM best practices. Benefits of SM use emphasize enhanced and efficient communication and increased access to care. Care team members incorporate SM into their daily clinical practices, using it to provide services before, during, and after clinical encounters as a best practice. SM users suggest improvements in veteran care, clinical team workflow, and efficient use of health resources. Clinical team members invested in the successful implementation of SM integrate SM into their daily practices to provide meaningful and useful veteran-centered care and improve workflow.Conclusion VA clinical care team members can use SM proactively to create an integrated SM culture. With adequate knowledge and motivation to proactively use this technology, all clinical team members within the VA system can replicate best practices shared by other clinical care teams to generate meaningful and useful interactions with SM to enrich veterans' health care experience.
Keywords: patient provider communication; messaging; ambulatory care/primary care; process improvement; diffusion of innovation